Primary Bilateral Non-Hodgkin's Lymphoma of the Adrenal Gland: A Case Report - Ahmed Amine Bouchikhi; Mohamed fadl Tazi; Driss Amiroune; Soufiane Mellas; Jalaledine El Ammari; Abdelhak Khallouk; Mohammed Jamal El fassi; Moulay Hassan Farih (Case Reports in Urology)
Primary bilateral non-Hodgkin's lymphoma (NHL) of the adrenal gland is a very rare entity. Indeed less than 60 cases have been reported in the literature. Hence, we report a case of high-grade lymphoma of both adrenal glands that was found in a young patient of 32 years of age. The patient was admitted in the emergency department of our hospital with a profile of hemorrhagic shock. After stabilization, the imaging investigations demonstrated large bilateral adrenal masses. The CT-scan guided biopsy of both adrenal glands allowed the diagnosis of primary bilateral adrenal NHL. The patient died after the first chemotherapy session. The presence of bilateral adrenal masses associated with a rapid increase of volume should raise the diagnosis of primary adrenal non-Hodgkin's lymphoma.